Att pröva sig mot tingen - Frykman, Jonas (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2011)
The classical attitude in fieldwork of ” being there” is to expose oneself to the conditions that the group under study are experiencing. The word "intersubjectivity" often is used to cover this way of doing research. But "subjectivity" in itself is running the risk of focusing on mental more than bodily processes, on words more than emotions and on interpretations more than insights. Even the phrase from Hannah Arendt of “visiting imagination” or the “lateral displacement” of Merleau-Ponty could point in such a direction. I have been using texts from two scholars: one by Billy Ehn when he is engaged in building a wall of stone by his house, and one by Bengt Nerman who similarly has described the physical encounter with stone and wood to discuss a more elaborate approach. Both texts in a marvelously detailed way inform the reader about what is to be learned from struggling with stone; how bodily insights beyond words are gained and how material culture reveals it nature of being so much more than scene, milieu, projections or representations. Fortitude from the stones are evoking a resonance and thus revealing the relational character between body and material culture. The work of the researcher of course is to transform such information into written ethnography.